Modified polyimide foam material and preparation method thereof
By introducing the hollow iron oxide/nickel nickel oxide complexes covered with graphite carbon as a flame retardant, the existing materials are used to solve the problem of insufficient flame retardant performance of the materials, and the efficient flame retardant and light quality of the materials are realized. Taking into account.
Patent Information
- Application Number
- CN202011230815.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-11-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-11-06
AI Technical Summary
The flame retardant properties of existing polyimide foam materials are insufficient, especially materials prepared by polyisocyanate, which cannot meet certain special requirements.
Introduce the littering of hollow iron oxide/nickel oxide complexes as flame retardants, which improves its flame retardant performance by binding with polytamide material.
It effectively improves the flame retardant performance of polylide foam materials, while maintaining the quality of the material, which is suitable for fire safety needs in high -end fields.
Smart Images

Figure BDA0002765141760000011 
Figure BDA0002765141760000021 
Figure BDA0002765141760000022
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyimide material preparation, and in particular to a modified polyimide foam material and a preparation method thereof. Background Art
[0002] Polyimide foam materials are a type of polymer material containing a large number of gas micropores / mesopores / nanopores. Compared with traditional foam plastics, polyimide foam not only has the characteristics of heat insulation, shock absorption, noise reduction, etc., but also has the advantages of high temperature resistance, low temperature resistance, intrinsic flame retardancy, radiation resistance, low smoke rate, etc., and has been widely and importantly used in many high-tech fields such as aerospace, aviation, space, shipbuilding, nuclear power, etc.
[0003] At present, the preparation method of polyimide foam mainly includes:
[0004] (1) Polyimide foam can be obtained by reacting the dibasic ester of tetrabasic acid with diamine. For example, BTDA and ethanol are refluxed to obtain the diethyl ester of BDTA, which is reacted with MPD to obtain a powdery product, which is heated at 300°C to obtain a polyimide foam.
[0005] (2) Synthesis by reaction of tetrabasic acid and diamine. For example, benzophenone tetraacid and MPD are dissolved in water, pyridine is used as a catalyst, and heated at 315°C to obtain polyimide foam material via a dipyridinium salt intermediate.
[0006] (3) Synthesis by reaction of dibasic anhydride or polybasic acid and polyisocyanate. Dibasic anhydride or polybasic acid reacts with polyisocyanate to generate unstable intermediate carbamic acid, which is then decarboxylated to form polyimide foam material. Dibasic anhydride or polybasic acid and polyisocyanate react by heating to generate gaseous CO2 foaming. For example, polyisocyanate, polybasic acid, furan alcohol foaming agent, and inorganic acid are sprayed at 80°C to prepare polyimide foam coating.
[0007] However, at present, the flame retardancy of the polyimide foam obtained by the above method still cannot meet some special requirements, especially the polyimide foam material prepared by polyisocyanate. In view of this, the present invention is proposed. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing a modified polyimide foam material, introducing a hollow iron oxide / nickel oxide composite coated with graphite carbon to improve the flame retardant properties of the polyimide foam material.
[0009] In order to achieve the above object, the present invention adopts the following technical solution.
[0010] In a first aspect, the present invention provides a modified polyimide foam material, which is prepared from raw materials including the following parts by weight:
[0011]
[0012]
[0013] Wherein, the flame retardant is a hollow iron oxide / nickel oxide composite coated with nitrogen-doped graphite carbon.
[0014] According to the modified polyimide foam material provided by the present invention, polyimide is modified using a hollow iron oxide / nickel oxide composite coated with nitrogen-doped graphite carbon. The metal oxide can promote the thermal oxidative degradation of the material. While effectively improving the flame retardant properties of the polyimide foam material, the hollow structure thereof will not increase the density of the obtained foam material, and the advantage of the light weight of the foam material can still be maintained.
[0015] According to the embodiment provided by the present invention, the modified polyimide foam material is prepared from raw materials including the following parts by weight:
[0016]
[0017] According to the embodiment provided by the present invention, in the hollow iron oxide / nickel oxide composite coated with nitrogen-doped graphite carbon, the sum of the mass of the iron oxide and the nickel oxide accounts for 60-70%, and the molar ratio of the iron to the nickel is 1:1-1.5. The flame retardant with a composition within this range has a better flame retardant effect.
[0018] According to an embodiment of the present invention, in the hollow iron oxide / nickel oxide composite coated with nitrogen-doped graphitic carbon, the diameter of the hollow part is 2-5 μm.
[0019] According to the embodiment provided by the present invention, the aromatic dianhydride is one or more of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenone tetracarboxylic dianhydride (BTDA), diphenyl ether tetracarboxylic dianhydride (ODPA), and biphenyl sulfone tetracarboxylic dianhydride (DSDA), but is not limited thereto.
[0020] According to the embodiment provided by the present invention, the polyisocyanate is one or more of polyphenyl polymethylene polyisocyanate (PAPI), diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI), but is not limited thereto.
[0021] According to an embodiment provided by the present invention, the polar solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.
[0022] According to an embodiment provided by the present invention, the fatty alcohol is at least one of methanol, ethanol, n-propanol, isopropanol, butanol, and isobutanol, preferably methanol or ethanol.
[0023] According to the embodiment provided by the present invention, the foam stabilizer is at least one of polyether siloxane, polymethyl siloxane and vinyl polysiloxane, and its function is to improve the foaming stability, micropore size and micropore distribution uniformity.
[0024] According to the embodiment provided by the present invention, the catalyst is one or more of isoquinoline, triethanolamine, triethylenediamine, stannous octoate, and dibutyltin dilaurate.
[0025] In a second aspect, the present invention provides a method for preparing a hollow iron oxide / nickel oxide composite coated with flame retardant nitrogen-doped graphite carbon, comprising:
[0026] (i) In situ growth of Fe-MOF-74 material on the surface of sulfonated polystyrene spheres to obtain Fe-MOF-74@PS;
[0027] (ii) Taking Fe-MOF-74@PS as the core, the nickel precursor was grown in situ to obtain a nickel precursor with a core-shell structure;
[0028] (iii) sintering the nickel precursor in an oxygen atmosphere to obtain a hollow iron oxide / nickel oxide composite;
[0029] (iiii) The above iron oxide / nickel oxide composite is mixed with ZIF-8 and calcined under nitrogen atmosphere to obtain a hollow iron oxide / nickel oxide composite coated with nitrogen-doped graphitic carbon.
[0030] In the preparation method provided by the present invention, sulfonated polystyrene balls are used as templates, a layer of Fe-MOF-74 material is coated on the sulfonated polystyrene balls, and then a nickel precursor is grown with this as the core, and the polystyrene balls and MOFs materials are carbonized and decomposed during high-temperature sintering under oxygen to form a cavity, leaving iron oxide coated on the inner wall of the cavity to obtain a nickel precursor with a core-shell structure. This method realizes a hollow structure, which is conducive to reducing the density of the foam material. On the other hand, the present invention coats ZIF-8 containing nitrogen-containing organic ligands on the surface of the positive electrode material, and the metal zinc volatilizes during calcination, and the organic ligands are carbonized and generate nitrogen-doped graphite carbon coatings under the catalysis of transition metal nickel, which has excellent flame retardant properties.
[0031] According to an embodiment provided by the present invention, in step (i), the mass ratio of the sulfonated polystyrene spheres to Fe-MOF-74 is 1:2-5.
[0032] The particle size of the sulfonated polystyrene sphere is 2-5 μm. When the hollow structure obtained within the ratio range is added to the foam material as a flame retardant, it can better maintain the balance between the density and mechanical properties of the foam material, and will not reduce the mechanical properties of the foam material without increasing the density of the foam material.
[0033] According to an embodiment provided by the present invention, in step (ii), the molar ratio of iron to nickel in the nickel precursor is 1:1-1.5.
[0034] According to an embodiment provided by the present invention, in step (iiii), the mass ratio of the iron oxide / nickel oxide composite to ZIF-8 is 6-7:4.5-6.
[0035] According to the embodiment provided by the present invention, in step (iii), the sintering temperature is 700-750° C., and the sintering time is 8-16 hours.
[0036] According to the embodiment provided by the present invention, in step (iii), the sintering temperature is 700-750° C., and the sintering time is 8-12 h.
[0037] According to the embodiment provided by the present invention, in step (iiii), the calcination temperature is 600-700° C., and the calcination time is 4-8 hours.
[0038] In a third aspect, the present invention provides a method for preparing the modified polyimide foam material, comprising the following steps:
[0039] (1) 100-150 parts by weight of aromatic dianhydride is dissolved in 100-150 parts by weight of polar solvent at 80-100° C., and then 8-15 parts by weight of fatty alcohol is added and refluxed at 60-80° C. to obtain a solution;
[0040] (2) adding 10-20 parts by weight of deionized water, 8-15 parts by weight of a foam stabilizer and 2-5 parts by weight of a catalyst to the above solution, stirring and dispersing at 50-80° C., then adding 5-15 parts by weight of a flame retardant, and continuing to stir and mix uniformly to obtain a suspension;
[0041] (3) adding 150-200 parts by weight of polyisocyanate to the above suspension, stirring to obtain a mixed slurry, and pouring the mixed slurry into a mold for free foaming to obtain a foam precursor;
[0042] (4) The foam precursor is first heated at 150-200°C for foaming, and then imidized at 250-300°C to obtain a modified polyimide foam material.
[0043] The modified polyimide foam material prepared by the present invention has the characteristics of low density, uniform pore size, high mechanical strength, excellent flame retardant performance, etc., and can meet the fire safety requirements of polyimide foam materials used in high-end fields such as aerospace.
[0044] Compared with the prior art, the present invention has the following technical effects:
[0045] The present invention uses a self-made nitrogen-doped graphite carbon-coated hollow iron oxide / nickel oxide composite as a flame retardant. The metal oxide can promote the thermal oxidation degradation of the material, has a good flame retardant effect, and will not increase the density of the foam material or reduce the mechanical strength of the foam material. The modified polyimide foam material has excellent flame retardant properties and mechanical properties while maintaining the advantage of light weight, thereby broadening the application range of isocyanate polyimide foam materials. DETAILED DESCRIPTION
[0046] Unless otherwise specified, all scientific and technological terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. All patents and publications related to the present invention are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, that is, including the contents specified in the present invention, but does not exclude contents in other aspects.
[0047] The preparation methods of the nitrogen-doped graphitic carbon-coated hollow iron oxide / nickel oxide composite and the modified polyimide foam material are described in detail below.
[0048] 1. Preparation method of hollow iron oxide / nickel oxide composite coated with nitrogen-doped graphite carbon
[0049] (i) Preparation of Fe-MOF-74@PS
[0050] The preparation of the Fe-MOF-74@PS includes: dispersing sulfonated polystyrene spheres in a solvent, adding 2,5-dihydroxyterephthalic acid and iron salt, reacting, and washing and drying the reaction mixture after the reaction is completed to obtain a template agent with Fe-MOF-74 growing on the surface of polystyrene microspheres, which is recorded as Fe-MOF-74@PS.
[0051] The iron salt is ferrous chloride or ferrous sulfate.
[0052] In some embodiments, the molar ratio of the 2,5-dihydroxyterephthalic acid to the iron salt is 1:2.
[0053] The reaction temperature is 100-150° C., and the reaction time is 12-48 hours. In some embodiments, the reaction temperature is 120° C., and the reaction time is 24 hours.
[0054] In some embodiments, the solvent is a mixed solvent of anhydrous ethanol, deionized water, and N,N-dimethylformamide (DMF), and the volume ratio of the three is 1:1:1.
[0055] In some embodiments, the mass ratio of the sulfonated polystyrene spheres to Fe-MOF-74 is 1:2-5.
[0056] In some embodiments, the particle size of the sulfonated polystyrene spheres is 2-5 μm.
[0057] The sulfonation method of the polystyrene spheres is not particularly limited and can be carried out according to any known method in the art. The purpose of the sulfonation treatment is to introduce sulfonic acid groups on the benzene rings of polystyrene, which can react with the hydroxyl groups on 2,5-dihydroxyterephthalic acid to form sulfonates, which are used to grow MOFs materials in situ on the polystyrene spheres after anchoring the ligands.
[0058] In some embodiments, the preparation of the Fe-MOF-74@PS includes: dispersing sulfonated polystyrene spheres in a mixed solvent of anhydrous ethanol, deionized water, and DMF in a volume ratio of 1:1:1, adding 2,5-dihydroxyterephthalic acid and FeSO4 in a molar ratio of 1:2, reacting at 120°C for 24 hours, and after the reaction is completed, washing and drying the reaction mixture to obtain a template having Fe-MOF-74 grown on the surface of polystyrene microspheres, which is recorded as Fe-MOF-74@PS.
[0059] (ii) In situ growth of nickel precursor
[0060] The preparation method of the nickel-manganese precursor comprises: simultaneously and continuously adding a nickel salt solution, a precipitant and a complexing agent into a reaction kettle containing Fe-MOF-74@PS, reacting until the product particle size D50 is 8-20 μm, and then terminating the reaction to obtain a coprecipitation reaction mixture; then aging, washing, solid-liquid separation, and drying the obtained solid to obtain a nickel precursor with a core-shell structure.
[0061] Specifically, the nickel salt is at least one of nickel sulfate, nickel nitrate, nickel acetate and nickel chloride.
[0062] According to some embodiments provided by the present invention, the concentration of the nickel salt solution is 1 to 3 mol / L.
[0063] According to some embodiments provided by the present invention, the precipitant is a sodium hydroxide solution with a concentration of 8 to 10 mol / L.
[0064] According to some embodiments provided by the present invention, the complexing agent is ammonia water with a mass fraction of 15-25%.
[0065] According to some embodiments provided by the present invention, during the reaction process, the reaction temperature is controlled to be 40-70° C., the pH is 11-12, and the ammonia content is 0.1-0.5 mol / L.
[0066] According to some embodiments provided by the present invention, the aging time is 12-24 hours.
[0067] Specifically, the washing comprises: washing with a sodium hydroxide solution having a mass fraction of 1-10% and deionized water in sequence.
[0068] The solid-liquid separation includes filtration, centrifugation or decantation, etc.
[0069] The drying temperature is 80-150° C., and the drying time is 12-24 hours, for example, vacuum drying at 100° C. for 24 hours.
[0070] According to some embodiments provided by the present invention, in the nickel precursor, the molar ratio of iron to nickel is 1:1-1.5.
[0071] In some embodiments, the preparation method of the nickel precursor includes: adding a nickel salt solution with a concentration of 1 to 3 mol / L, a sodium hydroxide solution with a mass fraction of 8 to 10 mol / L, and ammonia water with a mass fraction of 5 to 25% to a reactor containing Fe-MOF-74@PS simultaneously and continuously, reacting until the product particle size D50 is 8-20 μm, and terminating the reaction to obtain a co-precipitation reaction mixture; then aging, washing, solid-liquid separation, and drying the obtained solid to obtain a nickel precursor with a core-shell structure.
[0072] (iii) Preparation of hollow iron oxide / nickel oxide composites
[0073] The preparation of the hollow iron oxide / nickel oxide composite comprises: sintering the nickel precursor in an oxygen atmosphere to obtain the hollow iron oxide / nickel oxide composite.
[0074] Specifically, the sintering temperature is 700-750° C., and the sintering time is 8-16 hours.
[0075] (iiii) Preparation of nitrogen-doped graphitic carbon-coated hollow iron oxide / nickel oxide composites
[0076] The preparation method of the nitrogen-doped graphite carbon-coated hollow iron oxide / nickel oxide composite comprises: mixing the above iron oxide / nickel oxide composite with ZIF-8, and calcining under a nitrogen atmosphere to obtain the nitrogen-doped graphite carbon-coated hollow iron oxide / nickel oxide composite.
[0077] The organic ligand of the ZIF-8 contains both nitrogen and carbon. During calcination, the metal zinc volatilizes, the organic ligand carbonizes, and a nitrogen-doped graphite carbon coating layer is generated on the surface of the iron oxide / nickel oxide composite under the catalysis of transition metal nickel.
[0078] The preparation method of ZIF-8 is not particularly limited, and the ZIF-8 can be prepared by any method known in the art or purchased directly.
[0079] The mass ratio of the iron oxide / nickel oxide composite to ZIF-8 is 6-7:4.5-6.
[0080] The calcination temperature is 600-700° C., and the calcination time is 4-8 hours.
[0081] 2. Preparation method of modified polyimide foam material
[0082] The preparation of the modified polyimide foam material may be carried out with reference to the preparation of polyisocyanate polyimide foam, without any particular limitation.
[0083] According to an embodiment provided by the present invention, the method for preparing the modified polyimide foam material comprises:
[0084] (1) dissolving aromatic dianhydride in a polar solvent at 80-100° C. with stirring, then adding fatty alcohol and reacting under reflux at 60-80° C. to obtain a solution;
[0085] (2) adding deionized water, foam stabilizer and catalyst to the above solution, stirring and dispersing at 50-80° C., then adding flame retardant, continuing to stir and mix evenly to obtain a suspension;
[0086] (3) adding polyisocyanate to the above suspension, stirring to obtain a mixed slurry, and pouring the mixed slurry into a mold for free foaming to obtain a foam precursor;
[0087] (4) The foam precursor is first heated at 150-200°C for foaming, and then imidized at 250-300°C to obtain a modified polyimide foam material.
[0088] The dosage of each component is as follows:
[0089]
[0090] In some embodiments, the preparation method specifically comprises:
[0091] (1) dissolving aromatic dianhydride in a polar solvent at 80-100° C. with stirring, then adding fatty alcohol and reacting under reflux at 60-80° C. for 0.5-1 h to obtain a solution;
[0092] (2) adding deionized water, foam stabilizer and catalyst to the above solution, stirring and dispersing at 50-80° C., then adding flame retardant, continuing to stir and mix evenly to obtain a suspension;
[0093] (3) quickly adding polyisocyanate to the above suspension, stirring to obtain a mixed slurry, and pouring the mixed slurry into a mold for free foaming to obtain a foam precursor;
[0094] (4) The foam precursor is first heated at 150-200° C. for foaming for 1-2 hours, and then imidized at 250-300° C. for 1-2.5 hours to obtain a modified polyimide foam material.
[0095] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if no specific conditions are specified, the conditions described in the specification or the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0096] Example 1
[0097] 1. Preparation of flame retardant nitrogen-doped graphite carbon-coated hollow iron oxide / nickel oxide composites
[0098] (i) Sulfonated polystyrene spheres (particle size of 2 μm) were dispersed in a mixed solvent of anhydrous ethanol, deionized water, and DMF in a volume ratio of 1:1:1, and 2,5-dihydroxyterephthalic acid and FeSO4 in a molar ratio of 1:2 were added. The reaction was carried out at 120°C for 24 h. After the reaction was completed, the reaction mixture was washed and dried to obtain a polystyrene microsphere template with Fe-MOF-74 grown on the surface, which was denoted as Fe-MOF-74@PS, wherein the mass ratio of sulfonated polystyrene spheres to Fe-MOF-74 was 1:3.
[0099] (ii) 1.5 mol / L nickel sulfate aqueous solution, 8 mol / L sodium hydroxide solution and 20% ammonia water are added simultaneously and continuously to a reactor containing Fe-MOF-74@PS, and the reaction temperature is controlled to be 50°C, pH=11, and the ammonia content is 0.3 mol / L for reaction. The reaction is terminated when the product particle size is 10 μm. After aging for 24 hours, the mixture is washed with 5% sodium hydroxide solution and deionized water in turn to remove impurities. After solid-liquid separation, the mixture is vacuum dried at 100°C for 24 hours to obtain a nickel precursor with a core-shell structure; the molar ratio of iron to nickel in the precursor is 1:1.5.
[0100] (iii) sintering the nickel precursor in an oxygen atmosphere at 700° C. for 8 h to obtain a hollow iron oxide / nickel oxide composite.
[0101] (iiii) The iron oxide / nickel oxide composite and ZIF-8 were uniformly mixed in a mass ratio of 6:6, and calcined at 650° C. for 6 h in a nitrogen atmosphere to obtain a nitrogen-doped graphitic carbon-coated hollow iron oxide / nickel oxide composite, wherein the sum of the mass of the iron oxide and the nickel oxide accounted for 60%.
[0102] 2. Preparation of modified polyimide foam material
[0103] (1) 100 parts of BTDA were dissolved in 100 parts of DMF at 80° C. with stirring, and then 15 parts of methanol were added and refluxed at 65° C. for 1 hour to obtain a solution;
[0104] (2) adding 10 parts of deionized water, 10 parts of foam stabilizer polysiloxane and 5 parts of catalyst triethanolamine to the above solution, stirring and dispersing at 60° C., then adding 5 parts of the flame retardant prepared above, continuing to stir and mix evenly to obtain a suspension;
[0105] (3) quickly adding 200 parts of PAPI to the above suspension, stirring to obtain a mixed slurry, and pouring the mixed slurry into a mold for free foaming to obtain a foam precursor;
[0106] (4) The foam precursor is first heated at 180° C. for foaming for 2 h, and then imidized at 300° C. for 1 h to obtain a modified polyimide foam material.
[0107] Example 2
[0108] 1. Preparation of flame retardant nitrogen-doped graphite carbon-coated hollow iron oxide / nickel oxide composites
[0109] The present embodiment is different from the embodiment 1 in that the particle size of the sulfonated polystyrene spheres is 5 μm.
[0110] 2. Preparation of modified polyimide foam material
[0111] Same as Example 1.
[0112] Example 3
[0113] 1. Preparation of flame retardant nitrogen-doped graphite carbon-coated hollow iron oxide / nickel oxide composites
[0114] In this embodiment, the difference from Embodiment 1 is that in step (iiii), the iron oxide / nickel oxide composite and ZIF-8 are mixed in a mass ratio of 7:4.5.
[0115] 2. Preparation of modified polyimide foam material
[0116] Same as Example 1.
[0117] Example 4
[0118] 1. Preparation of flame retardant nitrogen-doped graphite carbon-coated hollow iron oxide / nickel oxide composites
[0119] Same as Example 1.
[0120] 2. Preparation of modified polyimide foam material
[0121] In this embodiment, the difference from Embodiment 1 is that the amount of the flame retardant is 10 parts.
[0122] Example 5
[0123] 1. Preparation of flame retardant nitrogen-doped graphite carbon-coated hollow iron oxide / nickel oxide composites
[0124] Same as Example 1.
[0125] 2. Preparation of modified polyimide foam material
[0126] In this embodiment, the difference from Embodiment 1 is that the amount of the flame retardant is 15 parts.
[0127] Comparative Example 1
[0128] The difference between this comparative example and Example 1 is that the flame retardant is graphite.
[0129] Comparative Example 2
[0130] The difference between this comparative example and Example 1 is that the flame retardant is red phosphorus.
[0131] Performance Testing
[0132] The density, compression strength, heat release rate, limiting oxygen index and vertical combustion of the foam material prepared above were tested according to the standards of compression GB / T 8813-2008, microcalorimeter ASTM D7309, limiting oxygen index GB / T2406-93, and vertical combustion UL94. The test results are shown in Table 1.
[0133] Table 1
[0134]
[0135]
[0136] It can be seen from the data in Table 1 that the modified polyimide foam material obtained in the embodiment of the present invention has significantly improved flame retardancy compared with the common flame retardant graphite and phosphorus flame retardant, and because the flame retardant used in the present invention has a hollow structure, the density of the obtained foam material is relatively small.
[0137] In the description of this specification, the description with reference to the terms "some embodiments", "other embodiments", "embodiment", "example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0138] Although the embodiments and examples of the present invention have been shown and described above, it is to be understood that the above embodiments and examples are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments and examples within the scope of the present invention.
Claims
1. A modified polyimide foam material, characterized in that: It is prepared from the following raw materials in parts by weight: Wherein, the flame retardant is a hollow iron oxide / nickel oxide composite coated with nitrogen-doped graphite carbon; The preparation method of the nitrogen-doped graphite carbon-coated hollow iron oxide / nickel oxide composite comprises: (i) In situ growth of Fe-MOF-74 material on the surface of sulfonated polystyrene spheres to obtain Fe-MOF-74@PS; (ii) Taking Fe-MOF-74@PS as the core, the nickel precursor was grown in situ to obtain a nickel precursor with a core-shell structure; (iii) sintering the nickel precursor in an oxygen atmosphere to obtain a hollow iron oxide / nickel oxide composite; (iiii) The above iron oxide / nickel oxide composite is mixed with ZIF-8 and calcined under nitrogen atmosphere to obtain a hollow iron oxide / nickel oxide composite coated with nitrogen-doped graphitic carbon.
2. The modified polyimide foam material according to claim 1, characterized in that: In the hollow iron oxide / nickel oxide composite coated with nitrogen-doped graphite carbon, the sum of the mass of the iron oxide and the nickel oxide accounts for 60-70%, and the molar ratio of iron to nickel is 1:1-1.5; the diameter of the hollow part is 2-5 μm.
3. The modified polyimide foam material according to claim 1, characterized in that: The aromatic dianhydride is one or more of pyromellitic dianhydride, biphenyltetracarboxylic dianhydride, benzophenone tetracarboxylic dianhydride, diphenyl ether tetracarboxylic dianhydride, and biphenyl sulfone tetracarboxylic dianhydride; the polyisocyanate is one or more of polyphenyl polymethylene polyisocyanate, diphenylmethane diisocyanate, toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate.
4. The modified polyimide foam material according to claim 1, characterized in that: The polar solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; the fatty alcohol is one or more of methanol, ethanol, n-propanol, isopropanol, butanol, and isobutanol.
5. The modified polyimide foam material according to claim 1, characterized in that: The foam stabilizer is one or more of polyether siloxane, polymethyl siloxane and vinyl polysiloxane; the catalyst is one or more of isoquinoline, triethanolamine, triethylenediamine, stannous octoate and dibutyltin dilaurate.
6. The modified polyimide foam material according to claim 1, characterized in that: In step (i), the mass ratio of the sulfonated polystyrene sphere to Fe-MOF-74 is 1:2-5; the particle size of the sulfonated polystyrene sphere is 2-5 μm; in step (ii), the molar ratio of iron to nickel in the core-shell structured nickel precursor is 1:1-1.5; in step (iiii), the mass ratio of the iron oxide / nickel oxide complex to ZIF-8 is 6-7:4.5-6.
7. The modified polyimide foam material according to claim 1, characterized in that: In step (iii), the sintering temperature is 700-750° C. and the sintering time is 8-12 hours; in step (iiii), the calcining temperature is 600-700° C. and the calcining time is 4-8 hours.
8. The method for preparing the modified polyimide foam material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) dissolving aromatic dianhydride in a polar solvent at 80-100° C. with stirring, then adding fatty alcohol and reacting under reflux at 60-80° C. to obtain a solution; (2) adding deionized water, foam stabilizer and catalyst to the above solution, stirring and dispersing at 50-80° C., then adding flame retardant, continuing to stir and mix evenly to obtain a suspension; (3) adding polyisocyanate to the above suspension, stirring to obtain a mixed slurry, and pouring the mixed slurry into a mold for free foaming to obtain a foam precursor; (4) The foam precursor is first heated at 150-200°C for foaming, and then imidized at 250-300°C to obtain a modified polyimide foam material.
9. Application of the modified polyimide foam material according to any one of claims 1 to 7 in the field of aerospace.
Citation Information
Patent Citations
High-nickel cobalt-free positive electrode material and preparation method thereof
CN111916726A